Otimização do processo decisório na área de supply chain com o uso da ferramenta da árvore de decisão - Romero, Rafael Longhi (2012)
Due to the fact that we are all subject to make subjective decisions that may undermine the financial health of an organization, the focus of this work consisted in building a decisionmaking model based on decision tree method applicable to everyday decisions of a company,with the goal not only to minimize subjectivity as well as to trace the process. The study was conducted by analyzing data from decisions taken by the department of supply Chain for a company of hidden identity, the choice of suppliers of ingredients for the most significant for this company. For both assigned and estimated the probability of occurrence of supplier change considering each ingredient according to the historical study. taking into account some factors that impact the Supply Chain area, such as: product price, distance from the supplier's production to the company`s facility, the payment terms and the product packaging, this last informed when there was an improvement in the operation. The objective was achieved once we reach a ratio of 81% correlation between the subjective decisions taken and decisions made using this tool for the cases tested. You could say that the model did not have its 100% ratio since although all factors guided the decision maker to choose the best choice but the organizational culture averse to change damaged this change. Other studies in various areas are needed to validate this technique, but for the Supply Chain area this technique has been validated, taking into account actual cases, which approximates the practical means of academia. It should be noted that the model developed has been used in practice in the area of supply chain management of the company in question.